Association Between SLC16A5 Genetic Variation and Cisplatin-Induced Ototoxic Effects in Adult Patients With Testicular Cancer - Drogemoller, Britt I (AMER MEDICAL ASSOC, 2022)
10.1001/jamaoncol.2017.0502